THE SIGNIFICANCE OF THE KHOJA AMIN MAUSOLEUM IN THE CULTURAL HERITAGE OF NAMANGAN (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a scholarly analysis of the historical origins, architectural structure, and the contemporary role of the Khoja Amin Mausoleum, located in the Namangan region, within the cultural heritage of Uzbekistan. As a pivotal site in the development of ancient Sufi schools, the mausoleum reflects the historical urbanization processes of Namangan and holds profound significance in the religious and educational life of the region. The research was conducted using historical sources, local archaeological data, and comprehensive architectural analysis.